Pemanfaatan Solar Cell sebagai Energi Alternatif Terbarukan untuk Listrik Panti Asuhan di Kabupaten Merauke - Kaikatui, Rapha Nichita; Andika, Adik Putra; Yusman, Nurjannah (AJAD : Jurnal Pengabdian kepada Masyarakat, 2025)
Abba Orphanage is an orphanage under the Abba Affection Foundation (YKSA) located in Merauke. This foundation specializes in serving and fostering indigenous Papuan children with dormitory education. Currently, the electrical capacity of the Abba Orphanage has an installed electrical power of 1300 VA and is not adequate to meet all daily electricity needs of the orphanage. This also causes a lack of lighting at the entrance of the orphanage along ±300m from the main road. So the purpose of this activity is to utilize the potential of solar energy based on solar cell technology in order to help meet the electricity needs of the orphanage. The installed technology is 2 solar cells with a capacity of 100 Wp each, Solar Charge Controller/MPPT 40A, Battery/ACCU with a capacity of 60AH, DC Step-Up and Step-Down Converters, DC lights, and control boxes. The technological results of this activity have been handed over to partners as well as training activities/workshops on equipment operation and maintenance are carried out. The electrical energy storage capacity of this device is 1440W with load usage for 6 hours/working day, which is from 18:00 WIT to 21:00 WIT for an estimated use for 2 days.